Inventory models for maturing and ageing items: cheese and wine storage. Issue 2 (2nd September 2019) - Zanoni, Simone; Zavanella, Lucio Enrico; Ferretti, Ivan
The greatest part of literature on inventory models deals with items that preserve their value over time or at least, deteriorate over time. This paper focuses on a special class of items (defined as 'maturing/ageing items') characterised by the increase of their value over time, when appropriately stored: e.g., items which improve their organoleptic and tasteful characteristics over time. The cases which inspired the present contribution belong to food production and supply, as in the case of matured cheeses (e.g., the well known Grana Padano), aged red wines (e.g., the well known Barolo) and aged spirits that, once bottled, acquire value over time. However, other types of products characterised by a 'maturing/ageing' process could be further identified. The present study introduces and discusses the inventory problem for this class of items, highlighting its peculiarities and its most relevant features. So as to focus on the several and attractive aspects which characterise the problem considered, an illustrative model is presented, with the aim of identifying the optimal maturing/ageing period.